Optimization of thermal characteristics of axisymmetric synthetic air jet impingement on flat surface - R. J. Talapati; N. S. Hiremath (Journal of Mechanical Engineering and Sciences, 2022)
The local heat transfer of axisymmetric synthetic air jet impinging on flat surface is investigated experimentally. Acoustic speaker is used for generation of synthetic air jet with cavity of cylindrical shape. The experiments is conducted for actuator frequency ranging from 50Hz to 400Hz, orifice diameter 2mm to 10mm, orifice plate thickness 2mm to 10mm, cavity diameter 50mm to 75mm, cavity depth 30mm to 60mm, jet to plate distance 16mm to 112mm. A steady heat flow is maintained on the flat surface. Local heat transfer characteristics on flat surface is found by thermal images using IR thermal imaging and thin foil technique. The experimental results reveals that the heat transfer is highly effected by frequency, orifice diameter, orifice plate thickness, jet to plate distance. However, cavity depth and cavity diameter has small influence on thermal performance. The higher cavity volume show more influence on heat transfer characteristics. An optimization of synthetic jet performance parameters is studied for maximum thermal performance in terms of heat transfer characteristics.